Lesson from the Past, Knowledge for the Future: Roles of Human Memories in Earthquake and Tsunami Narratives in Mentawai, Indonesia - Tulius, Juniator (UI Scholars Hub, 2020)
Oral traditions are an important part of the culture of most Indonesian communities. Mentawai, an ethnic group residing in Mentawai Islands of Indonesia, has various genres of oral tradition. Traditional knowledge and local wisdom pertaining to natural disasters are also part of their oral tradition. Mentawai Islands are located along active tectonic plates, where earthquakes commonly occur at various magnitudes. Records show that great earthquakes and tsunamis hit Mentawai Islands several times in 1797, 1833, 2007, and 2010. Surprisingly, earthquakes occurring some hundred years ago do not seem to appear in Mentawai oral tradition. This is slightly different from communities in Simeulue, Solomon, and Andaman Islands whose natives still remember some devastating catastrophes that occurred in the past. People’s collective memories play an important role in upholding significant messages from past natural disasters. Some of those messages contain important lessons on how to cope with natural disasters if they should occur again. As a result, the majority of inhabitants of those islands survived future catastrophes because they remembered the lessons contained in their oral tradition. This is totally different in Mentawai where more than 500 people died during the 2010 earthquake and tsunami. Because of this, the Mentawai case becomes an interesting topic of study. This paper aims, therefore, to find out the reasons behind this apparent lack of oral tradition pertaining to the earthquakes and tsunamis that occurred several hundred years ago.